Matilda - Dahl, Roald (UK, 1988)
Matilda Wormwood's father thinks she's a little scab. Matilda's mother spends all afternoon playing bingo. And Matilda's headmistress Miss Trunchbull? Well, she's the worst of all. She is a big bully, who thinks all her pupils are rotten and locks them in the dreaded Chokey.
Keywords: Adventure; Juvenile Fiction